Navigating Energy Sector Transitions: The Vital Role of Human Resource Development from Oil and Gas to Renewable Sources - Balushi, Khalil Al (Digital Repository of Theses, 2024)
The oil and gas industry is in the midst of a major transition as the world moves toward renewable energy sources and reduced carbon emissions. This energy transition poses an existential threat to traditional oil and gas companies, while also creating opportunities for those able to successfully adapt their business models. Human resource development (HRD) has a crucial role to play in enabling firm competitiveness and resilience during this industry transformation. This paper examines the role of HRD professionals and strategies in the oil and gas industry as companies navigate the shift to renewable energy. Specific HRD focus areas are identified based on a review of industry trends and scholarly literature. These include managing organisational culture and change, facilitating workforce retraining and talent development, cultivating innovation and intrapreneurship, developing leadership capability for uncertainty and transformation, enhancing employer branding and recruitment messaging, and providing employee support structures during periods of instability. The paper discusses how HRD efforts in these areas can aid renewal of competitive advantage via development of new revenue streams in renewable energy, efficiency improvements in existing oil and gas operations, or diversification into related industries less vulnerable to the renewable energy transition. The paper concludes that HRD represents a vital dynamic capability for firms in the oil and gas industry facing potential decline. By leveraging HRD strategies and resources, companies can proactively manage disruptive change, sustain core operations, identify emerging opportunities, develop new capabilities, and maintain an engaged, resilient workforce. The renewing role of HRD will growingly determine organisational success and even survival amidst the uncertainties of energy transition.